2020
DOI: 10.1101/2020.09.11.291427
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CUB and Sushi Multiple Domains 1 (CSMD1) opposes the complement cascade in neural tissues

Abstract: Schizophrenia risk is associated with increased gene copy number and brain expression of complement component 4 (C4). Because the complement system facilitates synaptic pruning, the C4 association has renewed interest in a hypothesis that excessive pruning contributes to schizophrenia pathogenesis. However, little is known about complement regulation in neural tissues or whether such regulation could be relevant to psychiatric illness. Intriguingly, common variation within CSMD1, which encodes a putative compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 97 publications
(128 reference statements)
2
29
0
Order By: Relevance
“…Mice with higher C4 GCN and increased C4 protein levels show aberrant neuronal development, including increased pruning, accompanied by schizophrenia-like behavioral traits [ 7 9 ]. Also linked to schizophrenia is a common intronic allele of the CSMD1 gene [ 3 , 10 ], which encodes a complement inhibitor expressed in neural tissue, including developing neurons [ 11 , 12 ]. CSMD1 deletion in mice leads to neurocognitive deficits [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mice with higher C4 GCN and increased C4 protein levels show aberrant neuronal development, including increased pruning, accompanied by schizophrenia-like behavioral traits [ 7 9 ]. Also linked to schizophrenia is a common intronic allele of the CSMD1 gene [ 3 , 10 ], which encodes a complement inhibitor expressed in neural tissue, including developing neurons [ 11 , 12 ]. CSMD1 deletion in mice leads to neurocognitive deficits [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the neurodevelopmental disorder schizophrenia, genome wide association studies have shown a correlation of a C4 isotype overexpression with disease development, and a polymorphism in the central nervous system (CNS) specific functional homologue of CR1, CSMD1 was identified as a risk factor [79][80][81]. Most recently, C4 overexpression was linked to hypo-connectivity in the prefrontal cortex, and schizophrenia-like symptoms in mice [82], and the current hypothesis for schizophrenia pathogenesis involves aberrant complement mediated synaptic pruning. Synaptic pruning onset was also documented during West Nile virus infection and in the neurodegenerative diseases Alzheimer's, Parkinson's, multiple sclerosis, frontotemporal dementia and spinal muscular atrophy [83][84][85][86].…”
Section: The Complement System As a Driver Of Pathogenesismentioning
confidence: 99%
“…Less active synapses are pruned away and one of the mechanisms guiding this process is activation of the complement system through the classical pathway with C4 cleavage, progressing further into the alternative pathway resulting in C3 cleavage [ 77 , 78 ]. In the neurodevelopmental disorder schizophrenia, genome wide association studies have shown a correlation of a C4 isotype overexpression with disease development, and a polymorphism in the central nervous system (CNS) specific functional homologue of CR1, CSMD1 was identified as a risk factor [ 79 , 80 , 81 ]. Most recently, C4 overexpression was linked to hypo-connectivity in the prefrontal cortex, and schizophrenia-like symptoms in mice [ 82 ], and the current hypothesis for schizophrenia pathogenesis involves aberrant complement mediated synaptic pruning.…”
Section: Introductionmentioning
confidence: 99%
“…Along with changes in Nf-κß signalling, alterations in Smad signalling have also been identified to be associated with changes in Csmd1 expression [ 13 , 15 , 28 ]. Csmd1 has also been implicated in the regulation of complement, where it primarily regulates the formation of the C3 convertase [ 7 , 10 , 11 , 29 ]. Recently Csmd1 KO has been shown to promote C3 deposition on the synapses promoting synaptic pruning in mice [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Csmd1 has also been implicated in the regulation of complement, where it primarily regulates the formation of the C3 convertase [ 7 , 10 , 11 , 29 ]. Recently Csmd1 KO has been shown to promote C3 deposition on the synapses promoting synaptic pruning in mice [ 29 ].…”
Section: Introductionmentioning
confidence: 99%